Makerspace como estrategia de enseñanza - aprendizaje de Biodiversidad con los estudiantes de sexto semestre de la carrera de Pedagogía de las Ciencias Experimentales Química y Biología - Chinlle Moyolema, Gloria Maribel (2024)
The aim of the present research work entitled "Makerspace as a teaching-learning strategy for Biodiversity", was to propose improvements in student learning through the activities described in the didactic guide, considering that they promote creativity, the development of reflective criteria, innovation, active participation, and the strengthening of the teacher-student bond. The problem lay in the need to create learning spaces where students can develop critical thinking and the lack of time required to teach complex subjects such as Biodiversity. The research approach was quantitative, with a nonexperimental, descriptive, bibliographic and field design. For data collection, a survey and questionnaire were used with 24 sixth semester students. According to the analysis and discussion of results, it is concluded that the implementation of the Makerspace can help to improve learning in a positive way, since it favors autonomous and collaborative learning, encouraging and motivating students, and at the same time promoting respect, tolerance, and understanding of the subject through active practice. In such a way that it manages to strengthen the retention of content and the reader's learning. It is recommended to promote the creation of spaces that favor the Makerspace, which are adapted to the needs of students, encouraging the university community to innovation, where the knowledge generated by the student is based on research and development of scientific projects.